2017
DOI: 10.1557/jmr.2017.224
|View full text |Cite
|
Sign up to set email alerts
|

Reaction with organic halides as a general method for the covalent functionalization of nanosheets of 2D chalcogenides and related materials

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…2. IR spectrum of WS 2 has a broad and less intense peaks which are in good agreement with IR data of bulk WS 2 reported earlier [56][57][58]. IR spectra of PNA and its WS 2 nanocomposites show peaks around 3400 cm −1 due to the imine N-H stretching vibrations [59].…”
Section: Ftir Studiessupporting
confidence: 89%
“…2. IR spectrum of WS 2 has a broad and less intense peaks which are in good agreement with IR data of bulk WS 2 reported earlier [56][57][58]. IR spectra of PNA and its WS 2 nanocomposites show peaks around 3400 cm −1 due to the imine N-H stretching vibrations [59].…”
Section: Ftir Studiessupporting
confidence: 89%
“…In contrast, the 1T phase has a tetragonal symmetry, with an octahedral metal coordination, as the layers are offset from each other. The conductivity of 2H is semiconducting, whereas 1T is metallic, in which the latter is recognized for its reactivity towards functionalization , as well as enhancing electrochemical properties . Moreover, both edge and basal sites are active in 1T-phase TMDs, further improving the electrocatalytic performance. , With good conductivity, fast electron-transfer kinetics, and increased catalytic sites, these 1T-TMDs are anticipated to promote the signal transduction of an electrochemical biosensor.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The nucleophilic reaction occurs because of electron transfer between the metallic 1T phase and the halide, resulting in forming the covalent C−S bond. Interestingly, semiconducting sheets of the stable 2H form have been functionalized by reaction with iodobenzenes in the presence of a Pd 0 catalyst . It has also been shown that other organic bromides and iodides including certain fluorophores react with the MoS 2 sheets forming C−S bonds.…”
Section: Methodsmentioning
confidence: 99%